Preflight characterization of the BLAST-TNG receiver and detector arrays - Lourie N. P.; Ade P. A. R.; Angile F. E.; Ashton P. C.; Austermann J. E.; Devlin M. J.; Dober B.; Galitzki N.; Gao J.; Gordon S.; Groppi C. E.; Klein J.; et al. (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy IX, 2018)
The Next Generation Balloon-borne Large Aperture Submillimeter Telescope (BLAST-TNG) is a submillimeter mapping experiment planned for a 28 day long-duration balloon (LDB) flight from McMurdo Station, Antarctica during the 2018-2019 season. BLAST-TNG will detect submillimeter polarized interstellar dust emission, tracing magnetic fields in galactic molecular clouds. BLAST-TNG will be the first polarimeter with the sensitivity and resolution to probe the ∼0.1 parsec-scale features that are critical to understanding the origin of structures in the interstellar medium. BLAST-TNG features three detector arrays operating at wavelengths of 250, 350, and 500 m (1200, 857, and 600 GHz) comprised of 918, 469, and 272 dual-polarization pixels, respectively. Each pixel is made up of two crossed microwave kinetic inductance detectors (MKIDs). These arrays are cooled to 275 mK in a cryogenic receiver. Each MKID has a different resonant frequency, allowing hundreds of resonators to be read out on a single transmission line. This inherent ability to be frequency-domain multiplexed simplifies the cryogenic readout hardware, but requires careful optical testing to map out the physical location of each resonator on the focal plane. Receiver-level optical testing was carried out using both a cryogenic source mounted to a movable xy-stage with a shutter, and a beam-filling, heated blackbody source able to provide a 10-50 C temperature chop. The focal plane array noise properties, responsivity, polarization efficiency, instrumental polarization were measured. We present the preflight characterization of the BLAST-TNG cryogenic system and array-level optical testing of the MKID detector arrays in the flight receiver.